Influence of the forehand stance on knee biomechanics: Implications for potential injury risks in tennis players - Martin, C.; Sorel, A.; Touzard, P.; Bideau, B.; Gaborit, R.; DeGroot, H.; Kulpa, R. (Journal of Sports Sciences, 2021)
The open stance forehand has been hypothesized to be more traumatic for knee injuries in tennis than the neutral stance forehand. This study aims to compare kinematics and kinetics at the knee during three common forehand stroke stances (attacking neutral stance ANS, attacking open stance AOS, defensive open stance DOS) to determine if the open stance forehand induces higher knee loadings and to discuss its potential relationship with given injuries. Eight advanced tennis players performed eight repetitions of forehand strokes with each stance (ANS: forward run and stroke with feet parallel with the hitting direction, AOS: forward run and stroke with feet perpendicular to the hitting direction, DOS: lateral run and stroke with feet perpendicular to the hitting direction) at maximal effort. All the trials were recorded with an optoelectronic motion capture system. The flexion-extension, abduction-adduction, external-internal rotation angles, intersegmental forces and torques of the right knee were calculated. Ground reaction forces were measured with a forceplate. The DOS increases vertical GRF, maximum knee flexion and abduction angles, range of knee flexion-extension, peak of compressive, distractive and medial knee forces, peak of knee abduction and external rotation torques. Consequently, the DOS appears potentially more at risk for given knee injuries.